Tin sulfide nanofiber film as well as preparation method and application thereof
By uniformly coating tin sulfide on nanocellulose, a tin sulfide nanofiber film was prepared, which solved the problems of unevenness and activity weakening of tin sulfide particles during interface regulation in lithium metal batteries, and achieved high cycle stability and rate performance of lithium metal batteries.
Patent Information
- Application Number
- CN202510087617.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-20
AI Technical Summary
In the prior art, when tin sulfide particles are used as interface control materials in lithium metal batteries, due to the adhesive coverage and uneven distribution, lithium dendrites growth and instability of interface electrolyte membrane SEI, affecting the cyclic stability of lithium metal batteries.
By uniformly covering tin sulfide on nanocellulose, using the mesoporous network and film-forming characteristics of the nanocellulose, a supported tin sulfide nanofiber film is prepared, used for the separator interlayer of lithium metal batteries, forming an artificial interface protective film rich in lithium sulfide and a lithium tin alloy interface layer.
The tin sulfide nanofiber film can react in situ with lithium metal to form a uniform lithium tin alloy and lithium sulfide, promote uniform deposition of lithium metal, inhibit dendrites, and significantly improve the cycle stability and rate performance of lithium metal batteries.
Smart Images

Figure CN119875171A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a tin sulfide nanofiber film and a preparation method and application thereof. Background Art
[0002] Lithium metal anode has a very high theoretical specific capacity (3860mAh / g) and can be used to build the next generation of high energy density lithium metal batteries. However, the interface of lithium metal anode is unstable, which leads to the growth of lithium metal dendrites, seriously affecting the life and safety of lithium metal batteries.
[0003] Based on this background, people are committed to stabilizing the lithium metal anode by optimizing the lithium metal anode interface. One strategy is to change the composition and type of the electrolyte. For example, high concentrations of lithium salts and electrolyte additives (lithium nitrate, ethylene carbonate, etc.) can promote the uniform deposition of lithium metal and improve the cycle performance of lithium metal batteries. However, high concentrations of lithium salts give the electrolyte a high viscosity, which is not conducive to its penetration into the electrode. Constructing an artificial interface layer is also an effective way to improve its interfacial stability. Usually, some polymers (such as polydimethylsiloxane) or inorganic substances are coated on the surface of the lithium metal anode. The coating process has strict requirements on the operating environment, which greatly increases the difficulty of operation.
[0004] At present, there are also many studies that use functional coating layers to modify the diaphragm to improve the cycling stability of lithium metal; Patent Publication No. CN116470237A discloses that the raw materials for preparing the coating layer usually include inorganic non-metallic ceramic particles, ion sieves and binders; for example, antimony fluoride is formed on one side of the diaphragm through a binder, and the molecular sieve is formed on the other side of the diaphragm through a binder. The above methods achieve the function of coating by adding binders and other means, and their application in high energy density lithium metal batteries is limited. The latest research has found that when tin sulfide is used as a coating material, it can react with lithium metal in situ electrochemically to form a lithium-philic lithium-tin alloy to induce uniform deposition of lithium metal, and the production of lithium sulfide can improve the stability of the interface electrolyte membrane SEI and inhibit lithium dendrites. However, due to the powder characteristics of tin sulfide particles, they often rely on binders to coat the diaphragm or lithium metal surface, resulting in the activity of tin sulfide particles being weakened by the binder coverage. At the same time, the particles are unevenly distributed and have gaps, resulting in uneven distribution of reaction sites and ions, affecting the formation of a highly uniform SEI layer and affecting the cycling stability of lithium metal. Therefore, the method of directly using tin sulfide particles to improve the stability of lithium metal anode has limitations.
[0005] The inventor's previous work shows that cellulose materials are derived from forest grasses, and hydroxyl groups are evenly distributed on their surfaces. They have a three-dimensional network structure with uniform pore size distribution, papermaking film-forming properties, and degradability, which provides the possibility for designing a flexible self-supporting interface protective layer with uniform void characteristics. For example, patent authorization number CN115149209B discloses that cellulose extracted from common plants in nature is combined with zirconium ions to make modified nanocellulose membranes, which significantly improve the rate performance of aqueous zinc ion batteries or lithium ion batteries. However, the above patent only utilizes the ionic crosslinking effect between the zirconium ions of soluble zirconium salts and the hydroxyl groups on the surface of nanocellulose. In essence, it is still a nanocellulose material, which uses a porous three-dimensional network to improve ion transmission, does not react with the lithium metal negative electrode, and is difficult to regulate the physical and chemical properties of the lithium metal interface electrolyte interface membrane, and cannot effectively protect lithium metal, so its application in high energy density lithium metal batteries is limited.
[0006] To this end, we hope to develop a self-supporting tin sulfide nanofiber film with uniform pore size, anti-lithium dendrite, and lithium metal electrolyte interface film for use in the separator interlayer to protect lithium metal. Summary of the invention
[0007] The present invention provides a tin sulfide nanofiber film and a preparation method and application thereof, the purpose of which is to solve the above-mentioned problems existing in the background technology.
[0008] In order to achieve the above-mentioned purpose, the embodiments of the present invention provide a tin sulfide nanofiber film and its preparation method and application. The present invention uniformly coats tin sulfide on nanocellulose for the first time, fully utilizes the intrinsic mesoporous network and film-forming properties of nanocellulose, and prepares a self-supporting tin sulfide nanofiber film, which can effectively solve the adverse effects of the traditional tin sulfide particle interface control strategy. At the same time, the present invention uses nanocellulose to prepare a tin sulfide nanofiber film with high value, which has uniformly distributed mesopores and can homogenize the distribution of lithium ions. The lightweight self-supporting tin sulfide interface layer can react with lithium metal in situ to form a lithium-philic lithium-tin alloy and a lithium sulfide-rich solid electrolyte interface film SEI, which promotes the uniform deposition of lithium metal and inhibits dendrite growth, thereby improving the cycle stability of lithium metal batteries.
[0009] An object of the present invention is to provide a method for preparing a tin sulfide nanofiber film, comprising the following steps:
[0010] S1: taking nanocellulose powder and adding deionized water, and obtaining nanocellulose dispersion after ultrasonic dispersion;
[0011] S2: adding a soluble tin salt into the nanocellulose dispersion, and obtaining a nanocellulose dispersion containing tin ions after ultrasonic dispersion;
[0012] S3: adding a soluble sulfide to the nanocellulose dispersion containing tin ions, stirring and reacting to obtain a tin sulfide nanofiber suspension, and obtaining a tin sulfide nanofiber film by suction filtration, washing and drying;
[0013] The nanocellulose surface of the tin sulfide nanofiber film has a uniform and dense tin sulfide coating layer.
[0014] Preferably, the soluble tin salt is any one of tin methane sulfonate, tin ethane sulfonate, tin dichloride or tin tetrachloride, and the concentration is 1 to 12 mmol / L.
[0015] Preferably, the soluble sulfide is any one of potassium sulfide, sodium sulfide, ammonium sulfide, thioacetamide or thiourea, and the concentration is 1 to 12 mmol / L.
[0016] Preferably, the stirring reaction time is 1 to 24 hours.
[0017] Preferably, the drying temperature is 40-120° C., and the drying time is 6-48 hours.
[0018] Based on an overall concept of the invention, an embodiment of the present invention provides a tin sulfide nanofiber film obtained by the above-mentioned preparation method. The tin sulfide nanofiber film is intended to form a uniform and dense tin sulfide coating layer on the surface of nanocellulose, which can react with lithium metal in situ electrochemically to generate lithium-philic lithium-tin alloy and lithium sulfide, thereby inducing uniform deposition of lithium metal and inhibiting dendrite growth.
[0019] Preferably, the porosity of the tin sulfide nanofiber film is 40% to 80%.
[0020] Preferably, the pore size of the tin sulfide nanofiber film is between 20 and 60 nm.
[0021] Preferably, the thickness of the tin sulfide nanofiber film is 1 to 60 μm.
[0022] The embodiments of the present invention also provide a tin sulfide nanofiber film obtained by the above-mentioned preparation method or the application of the above-mentioned tin sulfide nanofiber film in a lithium metal battery.
[0023] Reaction mechanism
[0024] The present invention adopts nanocellulose as a template and modifies it with tin sulfide to prepare a tin sulfide nanofiber film, which has the characteristics of nanocellulose: high mechanical strength, good flexibility, high thermal stability, smooth surface, light weight, low density, controllable porosity, and uniformly distributed mesopores; that is, on the basis of inheriting the platform advantages of nanocellulose solution processability and papermaking film-forming properties, a uniform and dense tin sulfide coating layer is formed on the surface of nanocellulose, which can be applied to lithium metal batteries to form an artificial interface protective film rich in lithium sulfide and a lithium-tin alloy interface layer, which serves as a layer of "skin" for lithium metal and inhibits the generation of lithium dendrites during the cycle, thereby extending the cycle stability of the lithium metal battery; at the same time, it can adjust the ion distribution, promote the uniform transport of lithium ions, and ensure the uniform deposition of lithium metal; it has been verified that the tin sulfide nanofiber film protective layer can inhibit the growth of lithium dendrites and improve the cycle stability of lithium metal.
[0025] The above scheme of the present invention has the following beneficial effects:
[0026] (1) Compared with pure nanocellulose film, the unique tin sulfide nanofiber network of the tin sulfide nanofiber film of the present invention can react with lithium metal in situ to form a uniform, continuous, lithium-philic lithium-tin alloy, promote the uniform nucleation and growth of lithium metal, and generate a solid electrolyte interface film SEI rich in Li2S, inhibit the growth of lithium dendrites, and further improve the rate cycling characteristics of lithium metal batteries.
[0027] (2) The tin sulfide nanofiber film of the present invention has higher porosity and ionic conductivity, which is beneficial to reducing the internal resistance of the battery and improving the rate performance of the lithium metal battery. The introduction of the inorganic non-metallic tin sulfide coating layer increases the thermal stability of the film, and can also shield the hydrogen bonds on the nanocellulose, improve the stability of the film electrolyte, and make the battery more long-lasting and stable. The thickness and porosity of the tin sulfide nanofiber film of the present invention can be adjusted to 1 μm, which is significantly lower than the conventional functional coating based on tin sulfide particles, and is beneficial to improving the overall energy density of lithium metal batteries.
[0028] (3) Compared with the traditional lithium metal interface protection method of directly coating tin sulfide particles, the tin sulfide nanofiber film of the present invention is flexible and self-supporting, has a three-dimensional nanofiber network structure and uniform mesopore distribution, and is also light and thin, which is in line with the current development trend of light and thin functional lithium metal protective films.
[0029] (4) The preparation process of the tin sulfide nanofiber film of the present invention is simple, and it fully inherits the intrinsic platform advantages of biomass cellulose materials. The above scheme reveals that inorganic non-metallic tin sulfide nanofibers can be prepared using nanocellulose as a one-dimensional template. The prepared tin sulfide nanofiber film has uniform pore characteristics, which can promote electrolyte infiltration, homogenize lithium ion distribution and accelerate lithium ion transmission, induce uniform deposition of lithium metal, and is beneficial to improving the cycle performance of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 These are scanning electron microscope images and optical images of the tin sulfide nanofiber film provided by an embodiment of the present invention; (a) scanning electron microscope image, (b) optical image;
[0032] Figure 2 The scanning electron microscope image and optical image of the tin sulfide powder provided in Comparative Example 1 of the present invention; (a) scanning electron microscope image, (b) optical image;
[0033] Figure 3 XRD patterns of the tin sulfide fiber film provided in the embodiment of the present invention, the tin sulfide provided in Comparative Example 1, and the original nanocellulose film provided in Comparative Example 2; wherein SnS2-CNF is the tin sulfide nanofiber film provided in the embodiment of the present invention, SnS2 is the tin sulfide in Comparative Example 1, and CNF is the original nanocellulose film provided in Comparative Example 2;
[0034] Figure 4 The tin sulfide nanofiber film provided by the embodiment of the present invention and the original nanocellulose film of comparative example 2 are applied to lithium metal symmetric batteries at 1 mAh cm -2 Morphology of lithium metal electrode after 200 cycles under the same conditions; (a) tin sulfide nanofiber film, (b) original nanocellulose film;
[0035] Figure 5 An X-ray photoelectron spectrum of the tin sulfide nanofiber film provided in an embodiment of the present invention applied to the lithium metal negative electrode interface in a lithium metal symmetric battery. DETAILED DESCRIPTION
[0036] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0037] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0038] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0039] Herein, “CNF” refers to pristine nanocellulose, and “SnS2-CNF” refers to tin sulfide nanofiber film.
[0040] In view of the existing problems, the present invention provides a tin sulfide nanofiber film and a preparation method and application thereof.
[0041] Example 1
[0042] This embodiment provides a method for preparing a tin sulfide nanofiber film.
[0043] The method of this embodiment specifically includes the following steps:
[0044] (1) Weigh 40 mg of nanocellulose powder, add a certain amount of deionized water, and ultrasonically obtain a nanocellulose dispersion;
[0045] (2) adding 0.5 g of tin tetrachloride crystals to the nanocellulose dispersion, mixing and then performing ultrasonic dispersion to obtain a nanocellulose dispersion containing tin ions;
[0046] (3) adding 0.5 g of thioacetamide to the nanocellulose dispersion containing tin ions, stirring and reacting for 6 hours; constructing a suction filtration device, adding deionized water for suction filtration and washing multiple times until the pH of the supernatant is neutral, so as to ensure that excess thioacetamide is washed away to prevent the synthesis reaction from continuing, and ultrasonically dispersing the collected precipitate in a certain volume of deionized water to obtain a uniform tin sulfide nanofiber suspension; taking a certain volume of the tin sulfide nanofiber suspension for suction filtration, heating and drying in an oven, and peeling off to obtain a tin sulfide nanofiber film, the thickness of which is measured to be 21 μm, and its SEM image is as shown in FIG. Figure 1 As shown, Figure 1 (a) It can be seen that the fibers of the tin sulfide nanofiber film are cross-linked with each other, with high porosity and uniform pore size; Figure 1 (b) shows the tin sulfide nanofiber film with a flat and smooth surface, which is yellowish brown.
[0047] Comparative Example 1
[0048] Weigh 0.28g of tin tetrachloride and add a certain amount of water to make a solution; add 0.5g of thioacetamide and stir to react for 6 hours; build a suction filtration device, add deionized water for multiple times to filter and wash until the pH of the supernatant is neutral to ensure that the excess thioacetamide is washed away to prevent the synthesis reaction from continuing, and heat and dry the collected precipitate and peel it off to obtain tin sulfide powder. Its SEM picture is as follows Figure 2 As shown in (a), under the condition that no nanocellulose is involved in the synthesis, the tin sulfide obtained is particles of different sizes. In the absence of a binder, it is impossible to obtain a flat tin sulfide protective layer. Figure 2 (b) The powder form shown.
[0049] Comparative Example 2
[0050] The difference between this comparative example and Example 1 is that 50 mg of nanocellulose powder is weighed, a certain amount of deionized water is added, and a nanocellulose dispersion is obtained after ultrasonic dispersion. A nylon filter membrane is used for filtration to form a film, a filtration device is built, the film is heated and dried in an oven, and a nanocellulose film is obtained by peeling off, and the measured thickness is 23 microns.
[0051] from Figure 3 It can be seen from the XRD diagram that the tin sulfide nanofiber film of the present invention has new peaks at 2θ of 28.19° and 50.06° compared with the nanocellulose film made from original cellulose. Comparison of the XRD diagram of tin sulfide can prove that the new peaks correspond to the characteristic peaks of tin sulfide, indicating that tin sulfide is successfully coated on the surface of nanocellulose.
[0052] The tin sulfide nanofiber film obtained in the embodiment is applied to a lithium metal symmetric battery. The lithium metal symmetric battery is -2 The current density is 1 mAh cm -2 After 200 cycles of area capacity, the lithium metal surface matching the tin sulfide nanofiber film showed a uniform and dense deposition layer (such as Figure 4 As shown in the figure, the lithium metal surface based on the original nanofiber film is loose and porous, and a dendrite-like lithium metal deposition layer appears. The above shows that the tin sulfide nanofiber film can even out the lithium ion transmission pathway, inhibit side reactions, and inhibit dendrite growth. Figure 4 XPS phase analysis of the lithium metal surface of the matching tin sulfide nanofiber film in a is performed. Figure 5 As shown, it can be seen that Li x Sn y alloy and Li2S, indicating that the tin sulfide nanofiber film can react with lithium metal in situ electrochemically to form lithium sulfide and lithium-tin alloy, thereby inducing uniform deposition of lithium metal and inhibiting dendrite growth.
[0053] Comparative Example 3
[0054] The difference between this comparative example and Example 1 is that the tin tetrachloride crystals are replaced with bismuth nitrate pentahydrate, and the other steps and parameters are the same as those in Example 1. Ultimately, it is impossible to synthesize a bismuth sulfide nanofiber film based on nanocellulose, and only a powdery bulk sample is obtained.
[0055] In summary, the preparation process of the tin sulfide nanofiber film of the present invention is simple, and the prepared tin sulfide nanofiber film has a three-dimensional mesoporous nanofiber network, combined with the papermaking film-forming properties of cellulose, and the properties of the inorganic non-metallic tin sulfide material and lithium metal spontaneously reacting to form lithium-tin alloy lithium-philic sites and lithium sulfide interface layers, so it can be used for battery diaphragm modification layers to protect lithium metal batteries, homogenize lithium ion distribution to promote uniform deposition of lithium metal, and inhibit lithium dendrite growth, greatly improving the cycle stability of lithium metal batteries. Compared with tin sulfide granular materials, the tin sulfide nanofiber film of the present invention is flexible and self-supporting, light and thin, with adjustable thickness, good mechanical strength, high porosity and uniform mesoporous distribution; the present invention organically links nanocellulose, inorganic non-metallic tin sulfide and lithium metal batteries, and explores the unique role of tin sulfide nanofiber films in the field of batteries, greatly improving the cycle performance of lithium metal batteries and improving the rate performance of batteries.
[0056] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a tin sulfide nanofiber film, characterized in that: The steps include: S1: taking nanocellulose powder and adding deionized water, and obtaining nanocellulose dispersion after ultrasonic dispersion; S2: adding a soluble tin salt into the nanocellulose dispersion, and obtaining a nanocellulose dispersion containing tin ions after ultrasonic dispersion; S3: adding a soluble sulfide to the nanocellulose dispersion containing tin ions, stirring and reacting to obtain a tin sulfide nanofiber suspension, and obtaining a tin sulfide nanofiber film by suction filtration, washing and drying; The nanocellulose surface of the tin sulfide nanofiber film has a uniform and dense tin sulfide coating layer.
2. The method for preparing a tin sulfide nanofiber film according to claim 1, characterized in that: The soluble tin salt is any one of tin methane sulfonate, tin ethane sulfonate, tin dichloride or tin tetrachloride, and the concentration is 1-12 mmol / L.
3. The method for preparing a tin sulfide nanofiber film according to claim 1, characterized in that: The soluble sulfide is any one of potassium sulfide, sodium sulfide, ammonium sulfide, thioacetamide or thiourea, and the concentration is 1-12 mmol / L.
4. The method for preparing a tin sulfide nanofiber film according to claim 1, characterized in that: The stirring reaction time is 1 to 24 hours.
5. The method for preparing a tin sulfide nanofiber film according to claim 1, characterized in that: The drying temperature is 40-120° C., and the drying time is 6-48 hours.
6. A tin sulfide nanofiber film obtained by the preparation method according to any one of claims 1 to 5.
7. The tin sulfide nanofiber film according to claim 6, characterized in that: The porosity of the tin sulfide nanofiber film is 40% to 80%.
8. The tin sulfide nanofiber film according to claim 6, characterized in that: The pore size of the tin sulfide nanofiber film is between 20 and 60 nm.
9. The tin sulfide nanofiber film according to claim 6, characterized in that: The thickness of the tin sulfide nanofiber film is 1 to 60 μm.
10. Use of a tin sulfide nanofiber film obtained by the preparation method according to any one of claims 1 to 5 or a tin sulfide nanofiber film according to any one of claims 6 to 9 in a lithium metal battery.
Citation Information
Patent Citations
A method for preparing and applying a zirconium ion-modified nanocellulose paper-based battery separator
CN115149209B
Diaphragm for high-rate dendrite-free lithium metal battery, preparation method of diaphragm and lithium metal battery
CN116470237A
Tin sulfide / nitrogen-doped carbonized bacterial cellulose negative electrode material for lithium-ion batteries and preparation method thereof
CN107317001A
High-performance two-dimensional metallic element doped SnS2-graphene-S composite material and preparation method and application thereof
CN109713255A
Lithium ion battery diaphragm based on coaxial carbon fiber and preparation method thereof
CN115036644A
Cited By
Perfluoropolyether blended PEGDE-based solid electrolyte and preparation method thereof
CN121416583A
Lewis acid metal ion-piperazine modified nano cellulose film as well as preparation method and application thereof
CN121748722A